Gambaran Kepuasan Peserta Program Pengelolaan Penyakit Kronis (PROLANIS) di Puskesmas Mamajang Kota Makassar - Muhammad Gilang Ramadhan; Salahuddin Salahuddin (Indonesian Journal of Health, 2025)
The background: In 2014 Indonesia introduced a non-communicable and chronic disease management program called the Indonesian Chronic Disease Management Program (PROLANIS). Patient satisfaction in the PROLANIS is an important benchmark for assessing the quality of health services provided by health facilities. The suitability of implementing PROLANIS at the Mamajang Community Health Center will be seen from the patient satisfaction survey. Research purposes: to find out the picture of PROLANIS patient satisfaction at the Mamajang Community Health Center. Method: This type of research uses observational preliminary study. Using sampling technique cluster sampling. The data collection technique is semi-structural interviews, then the data is analyzed descriptively and presented in the form of narratives and images. Results: 100% of patients are satisfied with the staff and 90.1% of patients are satisfied with the facilities and infrastructure as well as the programs and activities of the Mamajang Community Health Center. Obstacles encountered include places to take medicine and counseling. Conclusion: The implementation of PROLANIS at the Mamajang Community Health Center is very good in terms of staff, facilities and infrastructure as well as programs and activities.